Fracture of Nano and Engineering Materials and Structures
DOI: 10.1007/1-4020-4972-2_459
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Mechanisms of a Thin Elastic Plastic Laminate

Abstract: The fracture toughness of a polymer-metal laminate composite is obtained by mechanical testing of a specimen containing a pre-crack. The laminate is a material used for packaging. It consists of a thin aluminium foil and a polymer coating. A centre cracked panel test geometry is used. Each of the layers forming the laminate is also tested separately. The result is compared with the measured fracture strength of the individual layers. It is observed that the load carrying capacity increases dramatically for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Polymers films of low-density polyethylene (LDPE) and polyethylene terephthalate (PET) are widely used in packaging industries, and tearing is a common method of package-opening. Although there are many existing in-plane mode I studies on single layer as well as laminates of these thin polymer films (Kao-Walter 2004;Kao-Walter et al 2006;Andreasson et al 2014;Zhang et al 2016), not many out-of-plane investigations could be found in the literature (Kim and Karger-Kocsis 2004;Bjerkén et al 2006;Kao-Walter et al 2009, 2011Martínez et al 2010;Andreasson et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymers films of low-density polyethylene (LDPE) and polyethylene terephthalate (PET) are widely used in packaging industries, and tearing is a common method of package-opening. Although there are many existing in-plane mode I studies on single layer as well as laminates of these thin polymer films (Kao-Walter 2004;Kao-Walter et al 2006;Andreasson et al 2014;Zhang et al 2016), not many out-of-plane investigations could be found in the literature (Kim and Karger-Kocsis 2004;Bjerkén et al 2006;Kao-Walter et al 2009, 2011Martínez et al 2010;Andreasson et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studying the tearing of thin polymer laminates become involved as the films in the laminate respond differently under load compared to individual layer; this has been investigated by several authors (Bjerkén et al 2006;Andreasson et al 2014;Zhang et al 2016;Kao-Walter et al 2006, 2009, 2011Islam et al 2016). Kao-Walter et al (2011) investigated the LDPE-PET laminate under tearing and observed delamination in the interface which increased along with tear crack propagation.…”
Section: Introductionmentioning
confidence: 99%